Effect of scrubbing technique with mild self-etching adhesives on dentin bond strengths and nanoleakage expression - Ornnicha Thanatvarakorn (2018)
© Quintessenz. All right reserved. Purpose: To evaluate the effect of a scrubbing technique with one-step self-etching adhesives on bond strengths and nanoleakage expression at the resin/dentin interface. Materials and Methods: Flat human dentin surfaces bonded with one of two mild self-etching adhesives, SE One (SE) or Scotchbond Universal (SU) applied either with scrubbing or without scrubbing technique, were prepared (n = 5). The microtensile bond strengths (μTBS), SE micrographs of morphological changes on treated dentin surfaces, and expression of nanoleakage along the bonded dentin interfaces as shown with TEM were evaluated. μTBS data were analyzed using two-way ANOVA and the post-hoc t-test at the significance level of 0.05. Results: The scrubbing technique had a significant positive effect on the μTBS of SU (p < 0.05), while it produced no significant difference for SE (p > 0.05). Morphological evaluation of the treated dentin surfaces demonstrated that SU with scrubbing showed the highest etching ability, followed by scrubbing SE > nonscrubbing SE > nonscrubbing SU. In the nonscrubbing groups, nanoleakage formation using SU exhibited a reticular pattern throughout the hybridized complex, whereas with SE, water-tree nanoleakage was only found in the adhesive layer at dentinal tubule orifices. The scrubbing groups of both adhesives did not exhibit any nanoleakage expression. Conclusion: Using a scrubbing technique when applying mild self-etching adhesives could improve resin monomer infiltration into dentin, chase water on adhesive surfaces, and facilitate smear layer removal.